The Discussion About the Economics Paradigm - Lydeka, Zigmas (Ekonomika, 2000)
The article describes the concept of economics paradigm. The paradigm is understood as a fundamental theory, a system of attitudes a research methodology predominating in the economic science. The present concepts of the investigation of existence of an economic system could he conditionally divided into two groups: 1. The concepts of economic investigation stipulated by the paradigm of the traditional economy. The scientific research of this nature is based on the classical understanding that economic phenomena, naturally prone to constancy and striving for the state of equilibrium, are systematically arranged and in continuous development. Therefore, the proponents of conventional economics give their exclusive attention in the economic process to constance order, equilibrium, and sameness (relationship). The behaviour and states of economic systems change radically as they become more complex and conditions of their existence vary. In open systems, upon an increase of instability and disorder within them, the equilibrium is more likely to he disturbed and their behaviour is harder to foresee. The change of parameters in a complex economic system becomes stochastic, and unpredictable. The economics affected by systematic transformation is character by unlinear development, instability, disturbances of equilibrium, and critical moments the attempt to explain it using the framework of the classical paradigm is a rather challenging scientific task. Neoclassical, or equilibrium theories arc said to apply less for research of transitional period’ not only because they describe momentary situations disregarding their change in real time. 2. The concepts of economic research conditioned by the so-called new paradigm of economy. The scientific research of this nature is based on other methodological stipulations rather than traditional ones. There is a tendency to declare that the development of the animate and inanimate world, society and space, creative and natural economic processes is determined by the same laws. Theories of thermodynamics, natural sciences and mathematics, arc extremely popular in economic research: the theory of dynamic systems and nonlinear movement; the theory of synergy; the theory of disasters, self-organisation, chaos, bifurcation, etc. The attempt, to explain the dynamics, and transformational processes of complex systems supporting them with interdisciplinary research arc theoretically interesting and justifiable. In the article, the author relates the traditional and new paradigms of the economy, and employs in this particular research the indispensable concepts, laws and principles, methodological stipulations and hypotheses that are characteristic of these paradigms. In my opinion, none of the economic theories or concepts should he considered absolutely irrelevant, or, on the contrary, absolutely right. Only by selecting the rational moment. of each scientific approach and integrating them into a unified system of knowledge can we try to find a new and acceptable idea for the explanation of transformation processes in civilization of the and of the 20th century.